Minimally Invasive Dynamic Hip Screw Fixation for the treatment of stable Intertrochanteric Fractures of femur - Pandey, Bimal Kumar; Rijal, Kiran Prasad; Prasai, Tanup; Panthi, Sagar; Pradhan, Rabindra Lal; Sharma, Sashmit; Manandhar, Rajeev Raj; Lakhey, Shishir (Journal of Kathmandu Medical College, 2014)
Background: Trochanteric fracture is the commonest fracture in elderly people. These fractures carry risks associated with prolonged immobility. Early fracture fixation allowing early mobilization of the patients is the aim of the treatment. Dynamic hip screw and plate remains the most common method for treating stable intertrochanteric fractures. Minimal invasive technique has advantages of less blood loss, minimal soft tissue dissection, early mobilization, lesser requirement of analgesics and shorter hospital stay.Objectives: The study was done to evaluate the amount of intraoperative blood loss, reduction of post operative haemoglobin, requirement of post-operative analgesics and days of postoperative hospital stay in the patients of stable intertrochanteric femur fracture treated with minimal invasive dynamic hip screw (MIDHS).Methods: Twenty-five cases of stable intertrochanteric fractures of femur were treated with minimal invasive Dynamichip screw technique. Average blood loss during surgery, reduction of postoperative haemoglobin, requirement of post-operative analgesics and total days of postoperative hospital stay were studied.Results: Mean intraoperative blood loss was 53 ml, mean reduction of postoperative haemoglobin was 0.9 gm/dl. Average wound size was of five cm. Postoperative analgesic requirement was twice a day in an average and for five days. Mean hospital stay after surgery was five days.Conclusion: Minimal invasive Dynamic hip screw is a safe technique having advantages of less blood loss, minimal soft tissue dissection, lesser requirement of post-operative analgesics and shorter hospital stay in treating stable intertrochanteric fractures.DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11739  Journal of Kathmandu Medical CollegeVol. 2, No. 4, Issue 6, Oct.-Dec., 2013Page: 170-174